Social Media Marketing Analysis Shoes Bandung - Ningsih, Wida; Arifiani, Rahmawaty (Yayasan Pendidikan Belajar Berdikari, 2024)
This research will evaluate and assess the impact of social media marketing on purchasing decisions at Avicenna Shoes Bandung. The study's population consisted of unknown Avicenna Shoe users. The maholtra formula was then applied to a sample of 73 persons drawn from this demographic. The variables employed in this research are the dependent variable Purchasing Decisions and the independent variable Social Media. This study's sample strategy was purposive sampling, with data testing helped by SPSS 26 software. The findings revealed that: 1) Social Media Marketing has an impact on purchasing decisions.This research will evaluate and assess the impact of social media marketing on purchasing decisions at Avicenna Shoes Bandung. The study's population consisted of unknown Avicenna Shoe users. The maholtra formula was then applied to a sample of 73 persons drawn from this demographic. The variables employed in this research are the dependent variable Purchasing Decisions and the independent variable Social Media. This study's sample strategy was purposive sampling, with data testing helped by SPSS 26 software. The findings revealed that: 1) Social Media Marketing has an impact on purchasing decisions.